Tourist and recreational activity of patients at Wieniec-Zdrój Health Resort during rehabilitation - Lis, Patrycja (Who needs tourism?, 2024)
The aim is to analyze the free time of patients at Wieniec-Zdrój Spa, located in the Kuyavian-Pomeranian Voivodeship. The research interests include issues such as patients’ free time, its quantity and method of use. The free-time behavior of patients on rehabilitation was observed, both in the spa area and during sightseeing trips. An important element was the classification of the activities of patients and the creation of an original typology of residents visiting health resorts. The research shows that the tourist and recreational activity of patients is diverse and depends on many factors, as residents try to spend their free time actively. The following research methods were used: a diagnostic survey (the tools were a survey and interview questionnaire), participant observation and photographic documentation.